The Conception of Law-Consciousness in the Pre-Marxian Sociology - Šerpytytė, Rita (Problemos, 1986)
Methodological shifts in the historical development of the concept of law-consciousness are considered. Doctrines of law in the philosophy comprising the period from Antiquity until the 19th century are analysed. The conclusion is drawn out that in the pre-Marxian philosophy the problem of law was stated and solved in a speculative manner, that is, as a purely theoretical problem. At the same time it is pointed out that only the development of material life of society could provide the basis for the new, materialistic approach towards the problem of law-consciousness.